Pengaruh Sistim Penyimpanan dan Lama Penyimpanan Terhadap Mutu Fisik Tomat (solanum lycopersicum) - Breemer, Rachel; Pattiruhu, Gysberth (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
Tomatoes are one of the crops that can grow in both highland and lowland areas and have high economic value. This study aims to analyze the effects of storage systems and storage duration on the physical quality of tomatoes (Solanum lycopersicum). The physical quality of tomatoes observed includes weight loss, firmness, and color. This study used stretch film packaging, stretch film modified with the addition of 6% O2 and 8% CO2 gas, and no packaging, with storage durations of 4, 8, 12, 16, and 20 days. The results showed that the modified packaging could maintain the quality of fresh tomatoes for 20 days with a weight loss increase of 2.38%, firmness level of 0.85 kg/cm, and color change of 16.46.